ANALISIS BIAYA DAN PENDAPATAN PENGOLAHAN GONDORUKEM DAN TERPENTIN DI BEBERAPA PABRIK DI JAWA TENGAH - Sylviani Sylviani; Akub J Abdurachman (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
Collophonium industrial development in Central Java serves two purposes, i.e, a new source of income, and improving the product efficiency for Perhutani state forest enterprise.Based on research results on four collophonium industries, the production costs ranging from Rp 109.37 ta Rp. 140. 70 with an average of Rp 127.46/kg with 10% coefficient of variation. The production costs elements consisting of manufacturing cost (Rp 120.28/kg) representief 94% of the total costs and Rp 7.18/kg for administrative cost. The average Profit before tax for the mill run by Perhutani was found to be Rp 40.12/kg, while those run by the private sector was as high as Rp 44.66/kg.